WITH CAP REFORMS AND GATT: GREATER MARKET ACCESS FOR COCONUT PRODUCTS? - Aurora Alarde Regalado (International Coconut Community, 1994)
The coconut industry is undeniably an important feature in the economies of the Asia‑Pacific region. It is an important source of income and food. In Vanuatu, this industry contributes 41% to its total export earnings; 7.10% in the Philippines; and 8.91% in the Solomon Islands in 1992. This industry also provides sustenance to the people of Indonesia, Malaysia, India and Sri Lanka. Coconuts are major ingredients in many food preparations in these countries.